Mechanical determinants of faster change of direction speed performance in male athletes - dos Santos, T.; Thomas, C.; Jones, P. A.; Comfort, P. (The Journal of Strength and Conditioning Research, 2017)
Mechanical variables during change of directions, for example, braking and propulsive forces, impulses, and ground contact times (GCT) have been identified as determinants of faster change of direction speed (CODS) performance. The purpose of this study was to investigate the mechanical determinants of 180° CODS performance with mechanical characteristic comparisons between faster and slower performers; while exploring the role of the penultimate foot contact (PEN) during the change of direction. Forty multidirectional male athletes performed 6 modified 505 (mod505) trials (3 left and right), and ground reaction forces were collected across the PEN and final foot contact (FINAL) during the change of direction. Pearson's correlation coefficients and coefficients of determination were used to explore the relationship between mechanical variables and mod505 completion time. Independent T-tests and Cohen's d effect sizes (ES) were conducted between faster (n = 10) and slower (n = 10) mod505 performers to explore differences in mechanical variables. Faster CODS performance was associated (p = 0.05) with shorter GCTs (r = 0.701-0.757), greater horizontal propulsive forces (HPF) (r = -0.572 to -0.611), greater horizontal braking forces (HBF) in the PEN (r = -0.337), lower HBF ratios (r = -0.429), and lower FINAL vertical impact forces (VIF) (r = 0.449-0.559). Faster athletes demonstrated significantly (p = 0.05, ES = 1.08-2.54) shorter FINAL GCTs, produced lower VIF, lower HBF ratios, and greater HPF in comparison to slower athletes. These findings suggest that different mechanical properties are required to produce faster CODS performance, with differences in mechanical properties observed between fast and slower performers. Furthermore, applying a greater proportion of braking force during the PEN relative to the FINAL may be advantageous for turning performance.